Application of chitosan spraying on acclimatization success of tiger orchid (Grammatophyllum scriptum) plantlets - ARI PITOYO; MUTIA RIZKA HANI; ENDANG ANGGARWULAN (Smujo International, 2015)
Pitoyo A, Hani MR, Anggarwulan E. 2015.Application of chitosan spraying on acclimatization success of tiger orchid(Grammatophyllum scriptum) plantlets. Nusantara Bioscience 7: 185-191. In Indonesia, tiger orchid or anggrek macan(Grammatophyllum scriptum) is one of the orchid species that have been mass propagatedwith in vitro culture technique. Thesuccessful determinant of in vitro culture after planlet formation is acclimatization.Plantlet have faced with absolutely differentenvironmental condition between inside and outside bottle that potentially severe the survival of theplantlet.The objectives of thisresearch were to know theeffect of chitosan for success of chitosan spraying inacclimatization ofplantlets ofG. scriptumand to knowthe optimum concentration of chitosan that can help thesuccessful of the acclimatization of plantletsG. scriptum.This research used aCompletely Randomized Design (CRD) with four level concentrations of chitosan spraying, there were 0 g/L; 0,5 g/L; 0,75 g/L;1 g/L.Every treatment underwent 15 repetitions. The data taken on this research were qualitative and quantitative data. Qualitative data wasgot from observation of morphology and anatomy then it was analyzed descriptively. The quantitative data was got from percentage ofplantlets life, observation ofshoot length, leaves length, leaves width, number of leaves, number of shoot, index and density of stomatal.The quantitative data was analyzed byAnalysis of Variance (ANOVA), if there was a significant difference between treatment groupsthen followed byDuncan's Multiple Range Test (DMRT) at level significanceof5 %. The result of thisobservation indicated that theeffect of chitosanwassignificant on several parameters including width leaf,plantlets height,and stomatal index while the length andnumber of leaves were not significantly different. The concentration of chitosan real effected on these ranged from 0.5-0.75 g/L.Chitosan concentration at above of 0,75 g/L showed a negative influence on theacclimatization successfully ofplantletsG. scriptum.